HOMESCHOOLING PRIMAGAMA PALEMBANG DI ERA REVOLUSI INDUSTRI 4.0 - Ningsih, Arum Gati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The problem in this research is why the primagama homeschooling of Palembang became one of the alternative education in the city of Palembang ?, (2) how are the opportunities and challenges of education in primagama homeschooling Palembang in the era of industrial revolution 4.0? The purpose of this research is to find out and describe why primagama homeschooling Palembang is one of the alternative education in Palembang city and how the opportunities and challenges of education in primagama homeschooling Palembang in the era of industrial revolution 4.0. The method used is a qualitative ethnographic method. Data collection techniques used in this study were observation and interviews. The validity test of the data is done by extension of observation, increasing perseverance in research, triangulation, discussion, negative analysis. The analysis techniques used in this study are domain data, toxicity, complementary, theme culture analysis. The results of the study show that Palembang's primagama homeschooling is an alternative education in developing children's potential. Palembang's primagama homeschooling opportunity is to develop the potential of children in the era of industrial revolution 4.0, on the other hand Palembang's primagama homeschooling has challenges in empowering children's interests and potential so there is no misuse through technology in the face of 4.0 industrial revolution.